(untitled) (Research, Society and Development, 2021)
According to the Brazil Federal Constitution, housing is a fundamental right of the individual and is directly linked to the guarantee of human dignity. This paper aims to analyze the application of Federal Law 11888/08, which deals with public and free technical assistance for the design and construction of social housing, with regard to the potential benefits for families receiving up to three minimum wages. The research was carried out in the city of Teófilo Otoni-MG, and from the data obtained in printed documents made available by the Social Assistance Reference Center (CRAS-Sul), an analysis of the conditions of the houses, the profile of the families and the priority needs for the design of the project and free public support by technicians of civil engineering, urbanism and architecture were made. The poorest neighborhoods in the southern region of the city, classified as areas of risk and violence were the locus of the study. Data of garbage collection, channeled water and sewage, individual energy measurements, building of new rooms and bedrooms and accessibility were collected through documentary research. Based on this data, the neighborhoods and priority types of action for each neighborhood were listed. The results show that the neighborhoods Jardim São Paulo, Taquara, Cidade Nova, Vila Barreiros and Vila Esperança have the worst rates in terms of the variables analyzed, so they must have priority to receive the benefits of Federal Law No. 11,888 / 08. As a managerial implication in public administration, the involvement of new actors is suggested, with the elaboration of covenants and partnerships between the Municipal Executive and organizations that can facilitate public and free technical assistance, in the design and execution of works that benefit the identified homes.